Mutational spectrum of the CHAC gene in patients with chorea-acanthocytosis. - Dobson-Stone, C; Danek, A; Rampoldi, L; Hardie, R; Chalmers, R; Wood, N; Bohlega, S; Dotti, M; Federico, A; Shizuka, M; Tanaka, M; Watanabe, M; et al. (2002)
Chorea-acanthocytosis (ChAc) is an autosomal recessive neurological disorder whose characteristic features include hyperkinetic movements and abnormal red blood cell morphology. Mutations in the CHAC gene on 9q21 were recently found to cause chorea-acanthocytosis. CHAC encodes a large, novel protein with a yeast homologue implicated in protein sorting. In this study, all 73 exons plus flanking intronic sequence in CHAC were screened for mutations by denaturing high-performance liquid chromatography in 43 probands with ChAc. We identified 57 different mutations, 54 of which have not previously been reported, in 39 probands. The novel mutations comprise 15 nonsense, 22 insertion/deletion, 15 splice-site and two missense mutations and are distributed throughout the CHAC gene. Three mutations were found in multiple families within this or our previous study. The preponderance of mutations that are predicted to cause absence of gene product is consistent with the recessive inheritance of this disease. The high proportion of splice-site mutations found is probably a reflection of the large number of exons that comprise the CHAC gene. The CHAC protein product, chorein, appears to have a certain tolerance to amino-acid substitutions since only two out of nine substitutions described here appear to be pathogenic.